School reopening and risks accelerating the COVID-19 pandemic: A systematic review and meta-analysis protocol - Luís Carlos Lopes-Júnior (Public Library of Science (PLoS), 2021)
Background One of the most recent concerns of this pandemic regards the role of schools reopening in disease transmission, as well as the impact of keeping schools closed. While school reopening seems critical for the education and mental health of children, adolescents, and adults, so far the literature has not systematically reached a consensus whether to recommend the return to schools in a way that would be safe for students and staff. Objective To synthesize and critically evaluate the scientific evidence on the potential risk of accelerating the Coronavirus Disease 2019 (COVID-19) pandemic among children, adolescents, young adults, and adults with school reopening. Methods This systematic review and meta-analysis protocol was elaborated following the PRISMA-P. We will include all observational study designs, which report on the potential risk of accelerating the COVID-2019 pandemic with school reopening. Electronic databases included were MEDLINE/PubMed, Cochrane Library, EMBASE, Web of Science, SCOPUS and CNKI. Additional sources will be also retrieved, including Clinical trials.gov-NIH, The British Library, Pro Quest Dissertations Database, Public Health Gray Literature Sources and Health Evidence, Google Scholar, and pre-prints [medRXiv]. No restriction to language or date will be used as search strategy. In an independently manner, two investigators will select studies, perform data extraction, as well as perform a critical appraisal of the risk of bias and overall quality of the selected observational studies, based on their designs. The heterogeneity among the studies will be assessed using the I2 statistic test. According to the results of this test, we will verify whether a meta-analysis is feasible. If feasibility is confirmed, a random-effect model analysis will be carried out. For data analysis, the calculation of the pooled effect estimates will consider a 95% CI and alpha will be set in 0.05 using the R statistical software, v.4.0.4. In addition, we will rate the certainty of evidence based on Cochrane methods and in accordance with the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Expected results This systematic review and meta-analysis will provide better insights into safety in the return to school in the context of the COVID-2019 pandemic, at a time when vaccination advances unevenly in several countries around the world. Hence, consistent data and robust evidence will be provided to help decision-makers and stakeholders in the current pandemic scenario. PROSPERO registration number CRD42021265283; https://clinicaltrials.gov.